Using Simulations and Screencasts in Online Preclass Activities to Support Student Building of Mental Models - Deborah G. Herrington; Ryan D. Sweeder (MDPI AG, 2024)
As online learning and flipped classes become more important in chemistry instruction, the development of learning materials that can be used to support students' independent learning of conceptual chemistry content is critical. This paper summarizes the key findings from an eight-year investigation of effective practices for using simulations in preclass introductions to core chemistry concepts with a focus on supporting students' development of particulate-level models. Student learning gains for six core chemistry concepts were compared for students' independent use of a simulation using scaffolded instructions versus students' viewing a screencast of instructors modeling the use of the simulation to answer a series of questions. Though both approaches resulted in student learning gains and provided a solid foundation for subsequent instruction, the screencast approach provided additional benefits. These included avoiding potential simulation limitations and the ability to add instructional content to support student learning. Additionally, studying many iterations of assignments for several different topics yielded an assignment design framework that provides guidelines for instructors looking to create or use simulation-based preclass activities in the classroom to support student learning.